Carbon cloth loaded heterostructure material, preparation method and application thereof
Patent Information
- Application Number
- CN202410039669.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-11
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-01-11
AI Technical Summary
Existing lithium-ion battery anode materials suffer from problems such as low specific capacity, poor conductivity, and unstable cycle performance, which hinder the development of high-energy-density lithium-ion batteries.
Heterogeneous structural materials supported on carbon cloth, including carbon cloth, bimetallic sulfide salts, and nitrogen-doped graphene, form uniformly covered flake-like CoSnS through the Kirkendall effect, enhancing the material's conductivity and cycle stability.
It achieves a rich mesoporous network structure, exhibits long-term cycle stability and excellent rate capability, and demonstrates good flexibility and resistance to mechanical bending as a negative electrode material for lithium-ion batteries, making it suitable for flexible lithium-ion energy storage devices.
Smart Images

Figure CN117855438B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of bimetallic sulfide composite materials, specifically relating to a carbon cloth-supported heterostructure material, its preparation method, and its application. Background Technology
[0002] In recent years, with the growing acceptance of high-quality energy development and environmentally friendly strategies in the new era, humanity has shifted its focus from non-renewable and heavily polluting fossil fuels to new clean energy sources. Lithium-ion batteries have consistently been the preferred choice for green and environmentally friendly batteries. Continuous improvements in lithium battery production technology and cost reductions have led to their widespread application in many fields in recent years, with lithium-ion batteries dominating the portable electronics market. However, materials used as negative electrodes in lithium-ion batteries, such as carbon-based materials, metal oxides, and alloys, suffer from drawbacks including low lithium intercalation potential, easy lithium deposition, safety concerns, low specific capacity, large volume expansion, poor cycle performance, and voltage hysteresis, thus hindering the development of high-energy-density lithium-ion batteries. Therefore, significant efforts have been devoted to researching promising negative electrode materials.
[0003] Currently, single metal sulfide materials suffer from problems such as low specific capacity, poor conductivity, and unstable cycling performance. Therefore, improving the conductivity and cycling stability of metal sulfide materials is the key technical problem that this invention aims to solve. Summary of the Invention
[0004] The purpose of this invention is to provide a carbon cloth-supported heterostructure material, its preparation method, and its application, so as to solve the problems mentioned in the background art.
[0005] The objective of this invention is achieved as follows: a carbon cloth-supported heterostructure material, characterized in that: the heterostructure comprises carbon cloth, bimetallic sulfide salt and nitrogen-doped graphene, wherein the mass percentage content of carbon cloth and nitrogen-doped graphene is 89-90%, and the mass percentage content of bimetallic sulfide salt is 10-11%.
[0006] The bimetallic sulfide salt is uniformly covered on the carbon fiber rods of the carbon cloth in a scaly manner, and both the bimetallic sulfide salt and the carbon fiber rods are micron-sized.
[0007] The carbon cloth serves as a carbon fiber substrate with a heterogeneous structure.
[0008] Preferably, the bimetallic sulfide salt is selected from one of tin cobalt sulfide, tin iron sulfide, tin manganese sulfide, or tin magnesium sulfide.
[0009] Preferably, the scale size of the bimetallic sulfide salt is 5-8 μm, and the diameter of the carbon fiber rod is 10-12 μm.
[0010] A method for preparing a carbon cloth-supported heterostructure material, characterized in that the method includes the following steps:
[0011] Step S1: Ultrasonically clean the carbon cloth with acetone, then wash it with deionized water, and then dry it in a vacuum drying oven;
[0012] Step S2: Immerse the dried carbon cloth in a binder solution with carboxyl functional groups for 48 hours, then remove it and dry it in a vacuum drying oven.
[0013] Step S3: Nitrogen-doped graphene is refluxed with concentrated sulfuric acid at 120°C for 7 hours, and is denoted as hydroxylated nitrogen-doped graphene NG.
[0014] Step S4: Dissolve 13%-48% nitrate, 47.3%-89.5% SnCl2·6H2O, and 200% C6HN4 by mass in a reactor containing deionized water. Heat the reactor to 140°C and maintain the temperature at 140°C for 8 hours. After the reactor cools naturally to room temperature, remove the carbon cloth precursor, wash it with deionized water, and then dry it in an 80°C vacuum drying oven.
[0015] Step S5: Dissolve the sulfiding agent in deionized water, ultrasonically disperse the doped graphene NG in the above solution, transfer the solution to the reaction vessel, and put the carbon cloth containing the precursor back into the reaction vessel; then heat the reaction vessel to 140°C and maintain it at 140°C for 8 hours.
[0016] Step S6: After the reaction vessel has cooled naturally to room temperature, remove the sample, wash it with deionized water, and dry it in an 80°C vacuum drying oven to complete the preparation of the heterostructure material.
[0017] Preferably, in step S1, the carbon cloth is ultrasonically cleaned with acetone for 90 minutes, and then dried in a vacuum drying oven at 80°C.
[0018] In step S2, the dried carbon cloth is immersed in a binder solution with carboxyl functional groups for 48 hours, and then dried in a vacuum drying oven at 80°C.
[0019] Preferably, the binder with carboxyl functional groups in step S2 is polyacrylic acid (PAA).
[0020] Preferably, the nitrate in step S4 is a cobalt salt, zinc salt, iron salt, nickel salt, magnesium salt, or copper salt.
[0021] Preferably, the vulcanizing agent in step S5 is CH4N2S.
[0022] Preferably, the bimetallic sulfide salt is tin cobalt sulfide, and the carbon cloth-supported heterostructure is a CoSnS@NG heterostructure.
[0023] An application of a carbon cloth-supported CoSnS@NG heterostructure material, which is used to prepare a lithium-ion battery anode.
[0024] The inventive principle of a carbon cloth-supported CoSnS@NG heterostructure material:
[0025] The formation of CoSnS can be explained by the Kirkendall effect. When the CoSn- precursor of carbon cloth comes into contact with a CH4N2S solution, it reacts with CH4N2S to form CoSnS on the surface of the carbon fiber cloth. Simultaneously, the carboxyl groups of polyacrylic acid and the amino groups of thiourea undergo dehydration condensation to form amide bonds. CoSnS then acts as a covalent layer on the carbon nanofibers. 2+ and Sn 2+ The diffusion rate relative to S 2- The process is relatively rapid, thus the CoSn- precursor gradually transforms into a scaly structure, resulting in a highly representative morphology of CoSnS. Furthermore, the nitrogen-doped graphene surface in solution possesses hydroxyl functional groups, which continuously undergo dehydration condensation reactions with the amino groups in thiourea as CoSnS gradually covers the carbon fiber rods, forming a strong covalent bond with CoSnS.
[0026] Compared with the prior art, the present invention has the following improvements and advantages:
[0027] 1. A carbon cloth CoSn- precursor is generated by coating a carbon fiber rod with uniform flake-like tin cobalt sulfide, and then hydroxylated nitrogen-doped graphene (NG) is fused with the carbon cloth CoSn- precursor to form a carbon cloth-supported CoSnS@NG heterostructure material. The carbon cloth-supported CoSnS@NG heterostructure material has a rich mesoporous network structure, which demonstrates long-term cycling stability and excellent rate capability.
[0028] 2. By using carbon cloth-supported CoSnS@NG heterostructure material as a self-supporting flexible electrode for lithium ions, and assembling a soft-pack battery with carbon cloth-supported CoSnS@NG heterostructure material as the negative electrode and lithium sheet as the positive electrode, good cycle stability was observed, with no thermal runaway or volume expansion, and good flexibility and resistance to mechanical bending. At the same time, carbon cloth-supported CoSnS@NG heterostructure material, as a cycle-stable high-rate negative electrode material, has great application prospects in the fabrication of flexible lithium-ion energy storage devices. Attached Figure Description
[0029] Figure 1 The structural diagram shows the carbon cloth-supported CoSnS@NG heterostructure material.
[0030] Figure 2The XRD diffraction pattern of the carbon cloth-supported CoSnS@NG heterostructure material is shown.
[0031] Figure 3 The graph shows the cycle performance of carbon cloth-supported CoSnS@NG heterostructure material used in lithium-ion batteries.
[0032] Figure 4 The graph shows the cycling performance of carbon cloth-loaded CoSnS@NG heterostructure material in pouch cells under different bending conditions.
[0033] Figure 5 The graph shows the cycling performance of carbon cloth-loaded CoSnS@NG heterostructure material in pouch cells under different current densities.
[0034] Figure 6 The charge-discharge curves of carbon cloth-loaded CoSnS@NG heterostructure material used in pouch cells under different bending conditions are shown in the figure.
[0035] Figure 7 The safety performance of a lithium-ion battery with a carbon cloth-supported CoSnS@NG heterostructure material is illustrated.
[0036] Figure 8 The image shows the cutting effect of using carbon cloth-loaded CoSnS@NG heterostructure material for pouch batteries.
[0037] Figure 9 Scanning electron microscope image of carbon cloth-supported CoSnS@NG heterostructure material. Detailed Implementation
[0038] The invention will be further summarized below with reference to the accompanying drawings.
[0039] A carbon cloth-supported heterostructure material is disclosed, comprising carbon cloth, bimetallic sulfide salt, and nitrogen-doped graphene. The mass percentage content of carbon cloth and nitrogen-doped graphene is 89-90%, and the mass percentage content of bimetallic sulfide salt is 10-11%. The bimetallic sulfide salt is uniformly coated on the carbon fiber rods of the carbon cloth in a scaly manner. Both the bimetallic sulfide salt and the carbon fiber rods are micron-sized, and the carbon cloth serves as the carbon fiber substrate of the heterostructure.
[0040] Furthermore, the scale size of the bimetallic sulfide salt is 5-8 μm, and the diameter of the carbon fiber rod is 10-12 μm; the bimetallic sulfide salt is: tin cobalt sulfide, tin iron sulfide, tin manganese sulfide, or tin magnesium sulfide.
[0041] The bimetallic sulfide salt used in this embodiment is tin cobalt sulfide.
[0042] like Figure 1 , Figure 9As shown, a carbon cloth-supported CoSnS@NG heterostructure material includes carbon cloth, CoSnS, and nitrogen-doped graphene; CoSnS is uniformly covered on the carbon fiber rods of the carbon cloth in a hollowed-out scale-like manner; the mass percentage content of carbon cloth and nitrogen-doped graphene is 89-90%, and the mass percentage content of CoSnS is 10-11%; the carbon cloth serves as the carbon fiber substrate of the heterostructure, the size of the hollowed-out scale-like CoSnS is 5-8 μm, and the diameter of the carbon fiber rod is 10-12 μm.
[0043] A method for preparing a carbon cloth-supported CoSnS@NG heterostructure material, the method comprising the following steps:
[0044] Step S1: Ultrasonically clean the carbon cloth with 100ml of acetone for 90 minutes to thoroughly remove organic matter and other impurities from the surface of the carbon cloth; wash the pretreated carbon cloth with a large amount of deionized water and then dry it in a vacuum drying oven at 80℃.
[0045] Step S2: Soak the dried carbon cloth in 80ml of polyacrylic acid (PAA) solution for 48 hours, then remove it and dry it in a vacuum drying oven;
[0046] Step S3: Nitrogen-doped graphene is refluxed with concentrated sulfuric acid at 120°C for 7 hours, and is denoted as hydroxylated nitrogen-doped graphene NG.
[0047] Step S4: Dissolve 0.29g of Co(NO3)2·6H2O, 0.675g of SnCl2·6H2O, and 2g of C6HN4 in a reactor containing 75ml of deionized water. Place the carbon cloth treated in step S2 vertically in the reactor. Heat the reactor to 140℃ and maintain the temperature at 140℃ for 8 hours. After the reactor cools naturally to room temperature, remove the carbon cloth precursor, wash it with deionized water, and dry it in an 80℃ vacuum drying oven.
[0048] Step S5: Dissolve 0.72g CH4N2S in 75mL deionized water, ultrasonically disperse 0.5g doped hydroxylated nitrogen graphene (NG) in the above solution, and then transfer the solution to a 100mL reactor to generate carbon cloth (CoSn-) containing the precursor; put the carbon cloth (CoSn-) containing the precursor back into the reactor; then heat the reactor to 140℃ and maintain it at 140℃ for 8h.
[0049] Step S6: After the reaction vessel has cooled to room temperature naturally, take out the sample, wash it with deionized water and dry it in an 80°C vacuum drying oven to complete the preparation of the heterostructure.
[0050] The inventive principle of a carbon cloth-supported CoSnS@NG heterostructure material:
[0051] The formation of CoSnS can be explained by the Kirkendall effect. When the CoSn- precursor of carbon cloth comes into contact with a CH4N2S solution, it reacts with CH4N2S to form CoSnS on the surface of the carbon fiber cloth. Simultaneously, the carboxyl groups of polyacrylic acid and the amino groups of thiourea undergo dehydration condensation to form amide bonds. CoSnS then acts as a covalent layer on the carbon nanofibers. 2+ and Sn 2+ The diffusion rate relative to S 2- The process is relatively rapid, thus the CoSn- precursor gradually transforms into a scaly structure, resulting in a highly representative morphology of CoSnS. Furthermore, the nitrogen-doped graphene surface in solution possesses hydroxyl functional groups, which continuously undergo dehydration condensation reactions with the amino groups in thiourea as CoSnS gradually covers the carbon fiber rods, forming a strong covalent bond with CoSnS.
[0052] The prepared carbon cloth-supported CoSnS@NG heterostructure material was applied as a lithium-ion battery anode material.
[0053] Meanwhile, lithium-ion batteries were assembled using carbon cloth-loaded CoSnS@NG heterostructure material as raw material, and the performance of the lithium-ion batteries was tested.
[0054] Lithium-ion battery assembly: Electrochemical tests were conducted using CR2032 coin-shaped cells. The prepared CC@CoSnS@NG was used directly as the working electrode, and lithium foil was used as the counter electrode.
[0055] Two electrodes were cut into 12 mm diameter discs, with a CoSnS loading of approximately 0.12 g on the carbon cloth. Celgard 2400 was used as the separator, and 1 M LiPF6 was added to ethylene carbonate (EC) / diethyl carbonate (DEC) / dimethyl carbonate (DMC) (volume ratio 1:1:1) as the electrolyte. The battery was assembled in an argon-filled glove box, with H2O and O2 contents maintained below 0.1 ppm.
[0056] The assembled lithium-ion batteries underwent performance testing, and the test results are as follows: Figure 3 As shown, it can be observed that after 600 cycles at a current of 5 A / g, the capacity shows almost no decay, exhibiting high specific capacity and excellent cycling performance. A carbon cloth-supported CoSnS@NG heterostructure material is used as the anode, and lithium foil as the cathode.
[0057] like Figure 4 As shown, the pouch cell maintained excellent cycle performance under different bending conditions (90° and 180°) with a current density of 1 A / g.
[0058] like Figure 5The figure shows the rate performance of the pouch cell at different current densities. It can be seen that the cell exhibits good rate performance at current densities of 0.1 A / g, 0.2 A / g, 0.5 A / g, 1 A / g, 2 A / g, and 5 A / g, with reversible capacities of 512.8, 341.8, 298.6, 244, and 191.3 mAh g, respectively. -1 The entire battery retained 98.5% of its capacity and had a CE of approximately 100% after 100 cycles at 1 A / g, demonstrating good cycle stability.
[0059] like Figure 6 The figure shows the charge-discharge curve distribution of the pouch cell at bending angles of 0°, 60°, 90°, and 180°. The results show that the four curves almost completely overlap, indicating that bending deformation has little effect on voltage changes. To further confirm the good bending flexibility of the pouch cell, the assembled pouch cell was bent 180° to power a timer (3.0V, 0.3W).
[0060] like Figure 7 As shown, even after significant bending, the performance of the flexible pouch battery remains well maintained. The practicality and safety of lithium-ion batteries have always been a major concern, taking into account their safety performance; such as... Figure 8 As shown in the image, a cutting experiment was conducted on the pouch cell. It can be clearly observed from the photograph that the pouch cell maintained its initial state throughout the process, without volume expansion or thermal runaway. Furthermore, after two cuts, the output voltage of the pouch cell was 2.74V, only 0.08V lower than the initial voltage. Even cutting the pouch cell into three segments did not result in internal short circuits or burnout. These results demonstrate the great promise of carbon cloth-supported CoSnS@NG heterostructure materials in the fabrication of flexible lithium-ion batteries.
[0061] The above description is merely an embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principle of the present invention should be included within the scope of the claims of the present invention.
Claims
1. A carbon cloth-supported heterostructure material, characterized in that: The heterostructure comprises carbon cloth, bimetallic sulfide salt, and nitrogen-doped graphene, with the carbon cloth and nitrogen-doped graphene accounting for 89-90% by mass and the bimetallic sulfide salt accounting for 10-11% by mass. The bimetallic sulfide salt is uniformly covered on the carbon fiber rods of the carbon cloth in a scaly manner, and both the bimetallic sulfide salt and the carbon fiber rods are micron-sized. The carbon cloth serves as a heterogeneous carbon fiber substrate. The preparation method of carbon cloth-supported heterostructure materials is as follows: Step S1: Ultrasonically clean the carbon cloth with acetone, then wash it with deionized water, and then dry it in a vacuum drying oven; Step S2: Immerse the dried carbon cloth in a binder solution with carboxyl functional groups for 48 hours, then remove it and dry it in a vacuum drying oven. Step S3: Nitrogen-doped graphene was refluxed with concentrated sulfuric acid at 120 °C for 7 h, and this was denoted as hydroxylated nitrogen-doped graphene NG. Step S4: Dissolve 13%-48% nitrate, 47.3%-89.5% SnCl2·6H2O, and 200% C6HN4 by mass in a reactor containing deionized water. Heat the reactor to 140 ℃ and maintain the temperature at 140 ℃ for 8 h. After the reactor cools naturally to room temperature, remove the carbon cloth precursor, wash it with deionized water, and dry it in an 80 ℃ vacuum drying oven. Step S5: Dissolve the sulfiding agent in deionized water, ultrasonically disperse the doped graphene NG in the above solution, transfer the solution to the reactor, and put the carbon cloth containing the precursor back into the reactor; then heat the reactor to 140 °C and maintain it at 140 °C for 8 h. Step S6: After the reaction vessel has cooled naturally to room temperature, remove the sample, wash it with deionized water, and dry it in an 80 ℃ vacuum drying oven to complete the preparation of the heterostructure material.
2. The carbon cloth-supported heterostructure material according to claim 1, characterized in that: The bimetallic sulfide salt is selected from one of tin cobalt sulfide, tin iron sulfide, tin manganese sulfide, or tin magnesium sulfide.
3. The carbon cloth-supported heterostructure material according to claim 1, characterized in that: The bimetallic sulfide salt has a scale size of 5-8 μm and the carbon fiber rod has a diameter of 10-12 μm.
4. A carbon cloth-supported heterostructure material according to claim 1, characterized in that: In step S1, the carbon cloth is ultrasonically cleaned with acetone for 90 minutes, and then dried in a vacuum drying oven at 80 ℃. In step S2, the dried carbon cloth is immersed in a binder solution with carboxyl functional groups for 48 hours, and then dried in a vacuum drying oven at 80 ℃.
5. The carbon cloth-supported heterostructure material according to claim 1, characterized in that: The binder with carboxyl functional groups in step S2 is polyacrylic acid (PAA).
6. The carbon cloth-supported heterostructure material according to claim 1, characterized in that: In step S4, the nitrate is a cobalt salt, zinc salt, iron salt, nickel salt, magnesium salt, or copper salt.
7. The carbon cloth-supported heterostructure material according to claim 1, characterized in that: The vulcanizing agent in step S5 is CH4N2S.
8. The carbon cloth-supported heterostructure material according to claim 2, characterized in that: The bimetallic sulfide salt is tin cobalt sulfide, and the carbon cloth-supported heterostructure is a CoSnS@NG heterostructure.
9. The application of a carbon cloth-supported heterostructure material according to claim 8, characterized in that: The CoSnS@NG heterostructure material was used to prepare the negative electrode for lithium-ion batteries.
Citation Information
Patent Citations
Sulfur-doped pre-lithiated silicon-carbon composite material and preparation method thereof
CN111740084A
Carbon cloth loaded nitrogen-doped graphene material as well as preparation method and application thereof
CN112108169A
